The use of 32P Method to Evaluate the Growth of Lowland Rice Cultivated in a System of Rice Intensification (SRI) - A. Citraresmini; I. Anas; Nurmayulis Nurmayulis (Atom Indonesia, 2013)
A pot experiment has been conducted to evaluate the growth of the Dyah Suci, a lowland rice variety, in an SRI (System of Rice Intensification) planting system. The phosphorus-32 (32P) isotope technique was used to evaluate the growth of plants in relation with their phosphorus uptake. The uptake was assumed to vary in the same direction as the growth of the plant. The 32P uptake is assumed to vary in the opposite direction to the plant’s total phosphorus uptake. Here the 32P uptake is expressed in count per minutes (cpm) which is then transformed to disintegration per minute (dpm). The results show that, in terms of promoting the plant’s uptake of phosphorus, the SRI planting system is superior to the conventional planting system, and it is manifested in the higher dry weight of straw and grain. From this experiment it is concluded that the 32P method can be used satisfactorily as a tool for explaining therelation between P-uptake and plant growth.Received: 04 Juny 2013; Revised: 22 August 2013; Accepted: 30 August 2013